Methodology of research of quality of life of surgical patients in the process of physical rehabilitation. - Romanenko Y.N; Lyannoy J.O (Kharkov National Pedagogical University, 2011)
The methodological characteristics of research of quality of life of surgical patients are considered in the article. The main requirements to records keeping, collection and statistical processing of data are argued during research of quality of life in the process of physical rehabilitation. The main characteristics and quality of life research tools requirements were pointed out. We have chosen The Short Form (36) Health Survey (SF-36) for our research, which studies the life quality index according to 8 criterions. The additional methods of functional state research of patients after abdominoanterior wall hernia surgery were suggested.